Exploring maternal and child healthcare projects in South African communities through Ubuntu lens: an appreciative inquiry - S. Nyandeni; N. S. Raliphaswa; M. R. Musie; M. S. Maputle; R. Gundo; F. M. Mulaudzi; N. V. Sepeng (BMC, 2024)
Abstract Background Ubuntu, a Nguni Bantu term meaning "humanity towards other", embodies a philosophy of collectivism, interconnectedness and mutual respect, which is deeply ingrained in South African culture. Ubuntu led community-based collaborative projects enhance community engagement of several stakeholders to ensure improved health outcomes for the mothers and children in the region. Similarly, collaborations between universities are required to co-create evidence-based interventions with healthcare systems and communities to achieve healthcare objectives. This paper explores maternal and child healthcare (MCH) projects in South African communities through the Ubuntu lens, using an appreciative inquiry approach. Methods A Qualitative approach based on the 5-cycle of Appreciative Inquiry (AI) as proposed by Cooperrider and Srivastava were applied. A purposive sampling method was used to select participants (n = 14) who are members of the Ubuntu MCH project. Data was gathered through workshop group discussions. The interviews were audiotaped and transcribed verbatim. Data analysis followed the six steps of narrative analysis. Results Three main themes were identified: Academic growth of personnel; professional empowerment and Ubuntu mentorship. Conclusion This study confirms that the Ubuntu principles emphasises solidarity, cohesion, and collaboration. The study recommends leveraging on Ubuntu principles to strengthen maternal and child healthcare services, suggesting that such this approach can lead to more sustainable and impactful health improvements in South African communities.